REVEALING THE CONFORMITY PREPARATION FOR COOPERATIVE FINANCIAL REPORT OF SHARIA FINANCIAL SERVICES BASED ON PSAK SHARIA IN MUNICIPALITY AND BLITAR DISTRICT - Rumanintya Lisaria Putri, Rumanintya Lisaria Putri (Fakultas Ekonomi Universitas 45 Surabaya, 2019)
With the development of business or activities of the Islamic Financial Services Cooperative (KJKS) in Blitar municipality and district which is indicated by an increase in managed assets and the amount of income obtained from its business activities, KJKS managers must be able to account for all operational activities to members. Municipality and Blitar district governments through the Cooperative service and UMKM Blitar also demand accountability from KJKS management in the form of financial reports that can be used to evaluate and monitor performance. In the theory of information asymmetry, managers or leaders of Islamic Financial Services Cooperatives are most likely to make irregularities in the preparation of financial statements, even though the preparation of financial statements is governed by an accounting standard. The research entitled